Mastering Spark for data science : master the techniques and sophisticated analytics used to construct Spark-based solutions that scale to deliver production-grade data science products /: master the techniques and sophisticated analytics used to construct Spark-based solutions that scale to deliver production-grade data science products. (2017) - Morgan, Andrew; Amend, Antoine; Hallett, Matthew; George, David
No abstract available